Navigating adaptive approaches for development programmes - Pett, Jamie (ODI, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Thinking and Working Politically in development - Coalitions for Change in The Philippines - Sidel, John T.; Faustino, Jaime (The Asia Foundation, 2020)
The Asia Foundation and the Australian Embassy in the Philippines today released a new publication, Thinking and Working Politically in Development: Coalitions for Change in the Philippines. Written by London School of Economics and Political Science Professor John T. Sidel and The Asia Foundation’s Jaime Faustino, the book examines the first phase of the Coalitions for Change program (2012-2018) and the contributions to key development policy reforms in the Philippines. The book is a rigorous treatment of the Coalitions for Change program’s transformative policy reforms—alongside lessons from its failures—across diverse policy arenas and in a wide variety of cities and provinces. The chapters are organized thematically: excise tax reform (Chapter 2), land governance reform (Chapter 3), education (Chapter 4), electoral reform (Chapter 5), disaster risk reduction and management (Chapter 6), and subnational governance reform and conflict resolution in Mindanao (Chapter 7). The co-authors together combine an independent, academic perspective on the program’s impacts (Sidel) with a front-row view of doing policy reform in the Philippines – both its political and technical dimensions (Faustino). Based on the empirical research and comparative analysis undertaken by the authors, the book articulates – and substantiates – a strong set of arguments that help to explain the program’s mixed pattern of achievements and disappointments. Overall, the book concludes that the seven-year program achieved significant and sustainable impact using problem-driven, adaptive, and iterative approaches to developmental change. The authors assert the program was at the forefront of notable development approaches: aid effectiveness and development around thinking and working politically, doing development differently, and adaptive programming. Graham Teskey, an early advocate of ‘thinking and working politically’ explores how development agencies can replicate the conditions for success in his Afterword. With illustrative case studies and analyses, the book provides valuable lessons for policymakers, scholars, bilateral agencies, think-tanks, and anyone interested in successfully maneuvering the shifting dimensions of development in the Philippines and elsewhere.